A Rare Case of Metastatic Glioblastoma Diagnosed by Endobronchial Ultrasound-Transbronchial Needle Aspiration - Mais Al-Sardi; Ali Alfayez; Yazeed Alwelaie; Abdullah Al-Twairqi; Faris Hamadi; Khalid AlOkla (Case Reports in Pulmonology)
Glioblastoma is a common primary brain tumor that has a high mortality rate. Reports of intrathoracic metastases are uncommon, with the most commonly reported site for metastases are the lung and pleura. However, involvement of the mediastinum is not well documented, and few reports of confirmed mediastinal metastases diagnosed by endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) exist. Herein, we report a rare case of metastatic glioblastoma to the thorax. A lady in her 40s has been previously diagnosed with intracranial glioblastoma with multiple incidences of disease recurrence despite treatment with chemoradiotherapy, adjuvant chemotherapy, and repeated surgical resections. She presented with dyspnea and pleural effusion, for which radiological imaging revealed lung, pleural, and mediastinal lesions. Further diagnostic workup with EBUS and pleural fluid sampling confirmed metastatic disease to both sites. The pleural fluid showed highly atypical cells positive for GFAP, and EBUS-TBNA immunostains were GFAP, S100, and synaptophysin positive, giving an overall picture consistent with metastatic glioblastoma. The patient was referred for palliative care, and unfortunately, she passed away after several months.